On Farm Trial of Prostaglandin Based Estrus Synchronization Protocols in Selected Milk-shed Areas of Amhara Region, Ethiopia - Chekol Demis; Tesfaye Zewudie; Derib Aydefruhim; Wodimagegn Terefe (ANIMAL PRODUCTION, 2022)
The present study was conducted from 2019 to 2020 in the Debre Birhan area of the Amhara region, Ethiopia, aiming to evaluate the effect of single-dose prostaglandin hormone in dairy cows and heifers at the smallholder farmer level. A total of 458 dairy cows and heifers were treated with 2ml of Synchromate® hormone, and after 77.82±2.74 hours, 286 of which (62.4%) were reported to have manifested estrus signs. Insemination was performed to 215 animals, 71 animals were not inseminated (the time for AI was passed when checked by rectal palpation) because of later reports by farmers after the cessation of estrus periods. Of the 215 animals that were inseminated, 82 (38.1%) conceived, and from the 82 animals that conceived, 79 (96.3%) gave birth. Estrus response and conception rate have not shown a significant difference between parity and body condition scores. However, treatment to estrus interval has been found to be significantly (p<0.05) influenced by parity, cows had shorter intervals than the heifers. This study indicated that there were problems in the detection and reporting of estrus response by the smallholder farmers, hence, requiring continuous training on dairy cow management.